CODE-SWITCHING AND CODE-MIXING IN TRILINGUAL EDUCATION IN HONG KONG: A CASE STUDY - Wang, Lixun (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Classroom instructions in Hong Kong secondary school context often involve code-switching/code-mixing, with textbooks in English yet the lessons being taught in Cantonese (A variety of spoken Chinese) or a Cantonese/English mix. The code-switching/code-mixing instruction has been a common practice in Hong Kong classroom teaching. However, the Education Commission of Hong Kong considered code-switching/code-mixing instruction as the primary reason for students’ inadequate levels of English and Chinese. Therefore, the Government adopted the policy of ‘mother-tongue teaching’ to promote Chinese-medium instruction so as to reduce code-switching/code-mixing instruction. In this paper, firstly, a summary of the historical background of the Hong Kong language polices will be introduced. Secondly, the role of code-switching/code-mixing instruction in classroom teaching will be discussed by illustrating examples from a case study in a Hong Kong secondary school. Finally, the reasons behind using mixed code and its impact on student learning will be analyzed and discussed. A number of research methods were employed: questionnaire survey, student focus group interviews and classroom discourse analysis. The research findings show that students in the case study school found the use of mixed code beneficial even though the school language policy does not encourage code-switching/code-mixing instruction. We anticipate that this study will shed some light on the study of code-switching/code-mixing.